Phytochemical and Antidiabetic Study of Methanolic Extract of Portulaca oleracea L. (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Portulaca oleracea L. (P. oleracea), a globally distributed edible herb traditionally used in ethnomedicine, has gained scientific attention due to its broad pharmacological spectrum. This study aimed to isolate and characterize bioactive compounds from the methanolic extract of P. oleracea and evaluate its antidiabetic potential in alloxan-induced diabetic mice. The whole plant was subjected to cold maceration, followed by chromatographic fractionation and 1H NMRbased structural elucidation. Two pure compounds were isolated and tentatively identified as 5,6-Bis(nitrooxy)-3,4- dihydro-1,2,4-triazine and 3-[4-Hydroxy-3-(3,4,5-trihydroxy-6-hydroxymethyl-tetrahydropyran-2-yloxy)-phenyl]-3- methoxy-N-[2-(3-methoxybenzyl)butyl]acrylamide. In vivo antidiabetic activity was assessed in albino mice via oral administration of the extract (500 mg/kg body weight) over 14 days. Fasting blood glucose levels were significantly reduced (mean reduction: 59.0%) in treated diabetic mice compared to baseline. ELISA-based biochemical assays demonstrated that serum creatinine and uric acid levels remained within normal physiological ranges, suggesting no renal toxicity and a potential nephroprotective effect. These findings indicate that P. oleracea contains potent bioactive constituents with antidiabetic efficacy and renal safety, supporting its therapeutic potential as a natural agent for diabetes management.Dhaka Univ. J. Pharm. Sci. 24(2): 211-218, 2025 (December)